Development of diabetes mellitus associated with quetiapine: A case series. Issue 3 (January 2017) - Nanasawa, Hideki; Sako, Akahito; Mitsutsuka, Tomohiko; Nonogaki, Kaori; Kondo, Tadayuki; Mishima, Shuichi; Uju, Yoriyasu; Ito, Toshihiko; Enomoto, Tetsuro; Hayakawa, Tatsuro; Yanai, Hidekatsu
Abstract : Abstract: We aimed to describe the characteristics and clinical course of patients who developed diabetes associated with the use of quetiapine. This study included patients who received quetiapine for over a month between April 2008 and November 2013, and were diagnosed as having new-onset diabetes after initiation of quetiapine. We excluded patients who developed diabetes more than 1 year after discontinuation of quetiapine. We identified new-onset diabetes by hemoglobin A1c or prescriptions of antidiabetic drugs. Among 1688 patients who received quetiapine, hemoglobin A1c had been measured in 595 (35.2%) patients at least once during the observation period, and 33 (2.0%) patients had received hypoglycemic drugs. Eighteen (1.1%) patients were considered to have developed new-onset diabetes associated with quetiapine after a median of 1.6 years following initiation of quetiapine. Median (interquartile range) age was 54.5 (29.8) years, 8 patients were male, and median (interquartile range) duration of mental illness was 15.3 (13.8) years. Median hemoglobin A1c and body mass index (BMI) were 7.1 (1.4) % and 28.4 (7.0) kg/m 2, respectively. Seventeen patients had dyslipidemia when diabetes was discovered. All of these discontinued quetiapine within 3 months after the diagnosis of diabetes, and the diabetes in 4 patients had ameliorated without hypoglycemic drugs. Of 13 patients who had received either oral hypoglycemic drugs or insulin, 2 patients achieved well-controlled hemoglobin A1c without hypoglycemic drugs, and 10 patients had hemoglobin A1c 5.0% to 7.7% with the continued use of hypoglycemic drugs. We demonstrated that almost all patients who developed quetiapine-associated diabetes had dyslipidemia and increased BMI. There was no life-threatening hyperglycemia and diabetes was ameliorated just by discontinuation of quetiapine in several patients. The monitoring of metabolic parameters during antipsychotic treatment is important to diagnose and treat diabetes earlier.